An Eclectic Professional Development Proposal for English Language Teachers (2016)
This article reports a mixed-method research project aimed at improving the practices of public sector English teachers in Cali (Colombia) through a professional development program. At the diagnostic stage surveys, documentary analysis, and a focus group yielded the teachers’ profile and professional needs. The action phase measured the program’s impact via surveys, evaluation formats, a focus group, researchers’ journal, and documentary analysis. Findings revealed that an eclectic approach tailored to the participants’ needs and interests and a practice-reflection-theory cycle improved the teachers’ quality.